Analysis of Evaluation of Cognitive, Affective and Psychomotor Levels in RPP Aqidah Moral Class XI MA Muallimat Malang with Revised Bloom's Taxonomy - Shofiyulloh, Muhammad; Ghifari Nugraha, Muhamad; Fajarianti, Saudah Nur Fitria (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research uses Bloom's Taxonomy Theory and analyzes the Learning Implementation Plan (RPP) for Aqidah Akhlak lessons in Class XI Madrasah Aliyah Muallimat Malang City. Systematic data analysis is a descriptive qualitative research method. National Education focuses on cultivating students' talents/potential to become people who are devout/faithful, have good morals, insightful and responsible. In the Revised Method, Bloom's Taxonomy consists of three domains: the cognitive domain focuses on the intellectual aspect, the affective domain contains behavior and activities related to the application of the values of Islamic teachings, for example the application of behavior or customs, and the psychomotor domain focuses on the function of motor skills. or physical skills. and learning media such as direct learning, questions and answers, discussions etc. For research results related to implementation, deviant attitudes and actions, such as lying and lack of discipline. Based on data analysis of the results of the formulation of the RPP MA Muallimat Malang City, the presentation reached 64.5% at level C4.